Does Lack of "Genetic-Relative Family Health History" Represent a Potentially Avoidable Health Disparity for Adoptees?. Issue 12 (1st December 2016) - May, Thomas; Strong, Kimberly A.; Zusevics, Kaija L.; Jeruzal, Jessica; Farrell, Michael H.; LaPean Kirschner, Alison; Derse, Arthur R.; Evans, James P.; Grotevant, Harold D.
Abstract : Many adoptees face a number of challenges relating to separation from biological parents during the adoption process, including issues concerning identity, intimacy, attachment, and trust, as well as (for older adopted children) language and other cultural challenges. One common health challenge faced by adoptees involves lack of access to genetic-relative family health history (GRFHx). Lack of GRFHx represents a disadvantage due to a reduced capacity to identify diseases and recommend appropriate screening for conditions for which the adopted person may be at increased risk. In this article, we draw out common features of traditionally understood "health disparities" in order to identify analogous features in the context of adoptees' lack of GRFHx.